Collisions and collaboration the organization of learning in the ATLAS experiment at the LHC - Boisot, Max. (Oxford : Oxford University Press, 2011)
The Large Hadron Collider at CERN is the world's largest scientific experiment involving 3000 scientists. Here a team of organisation theorists collaborate with leading figures at CERN to understand how this project has been organised and what lessons can be learnt for the management of major projects and 'big science'.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Large Hadron Collider (France and Switzerland) -- Experiments -- Evaluation; Organizational effectiveness